Parsimony, phylogeny, and genomics - Albert, Victor A. (Victor Anthony), 1964- (Bioscience Oxford., 2005)
"This book examines the potential that parsimony analysis (cladistics) summarization method has for both structural and functional comparative genomic research"--Provided by publisher